Opciones tipo barrera sobre la tasa de cambio Peso/Dólar (2019)
This paper shows the results obtained from reviewing diverse existing methodologies for the valuation and risk measurement of European Barrier Options, mainly focusing in the revision of numerical methods. The results obtained corroborate that the Monte Carlo Simulations as a valuation methodology for path-dependentoptions satisfactorily converge on the analytical formulation. The best-fit results are obtained when applying the Variance Control Method of AntitheticVariables.